Q17: Given: a = i + j + k, a. b = 1 and a × b = j - k. Then, b is equal to
A. -2i
B. 2i + k
C. 3j
D. i
how?
Q17: Given: a = i + j + k, a. b = 1 and a × b = j - k. Then, b is equal to
A. -2i
B. 2i + k
C. 3j
D. i
how?
An idea might be to start by defining $\displaystyle \displaystyle \mathbf{b} = x\mathbf{i} + y\mathbf{j} + z\mathbf{k}$ so that you can get expressions for $\displaystyle \displaystyle \mathbf{a}\cdot\mathbf{b}$ and $\displaystyle \displaystyle \mathbf{a}\times\mathbf{b}$, which you then should be able to solve simultaneously for $\displaystyle \displaystyle x,y,z$...